Black carp RNF115 restricts IRF3/7-mediated antiviral signaling in innate immunity - Yixuan He; Qun Wang; Lili Xiao; Hui Wu; Jun Xiao; Jun Zou; Hao Feng (Water Biology and Security)
The Really Interesting New Gene (RING) ubiquitin E3 ligase family comprises a large number of members and plays a crucial role in the antiviral process. RING finger protein 115 (RNF115), also known as BCA2, Rabring7, or ZNF364, is a novel RING domain protein. In this paper, we cloned the RNF115 homologue from black carp (Mylopharyngodon piceus) and characterized it. The open reading frame of black carp RNF115 contains 933 nucleotides and encodes 310 amino acids. The C-terminal RING domain of RNF115 is highly conserved among various homologous species. Immunofluorescence assays revealed the cytoplasmic and nuclear distribution of RNF115 in the presence or absence of spring viremia of carp virus (SVCV) infection. Overexpression of RNF115 impaired interferon (IFN) and the related interferon-stimulated gene (ISG) mRNA expression, while upregulating SVCV replication. Ex vivo knockdown of RNF115 offered the host cells enhanced antiviral signaling. In vivo knockdown of RNF115 also strengthened black carp's antiviral capacity. Additionally, the results of a dual-luciferase reporter assay, plaque assay, and qRT-PCR assay demonstrated that co-transfection of RNF115 with IRF3/7 reduced IRF3/7-induced IFN transcription and antiviral ability. The association between RNF115 and IRF3/7 was detected by co-immunoprecipitation and immunofluorescence assays. Co-transfection of RNF115 with IRF3/7 also reduced the protein levels of IRF3/7, which were rescued by MG132. The enhanced K48-linked ubiquitination of IRF3/7 under the condition of RNF115 co-transfection implied the ubiquitin/proteasome degradation pathway catalyzed by RNF115. Cysteine 238 and 241 in the RING domain are the main enzyme active sites for RNF115, and the mutant C238/241A lost most of its ability to restrict IRF3/7. In conclusion, black carp RNF115 dampens IRF3/7-mediated IFN signaling through facilitating the ubiquitination and degradation of IRF3/7, which sheds light on the regulation of IFN signaling.